A qualitative investigation of models of community mental health care for women with perinatal mental health problems. (3rd September 2021) - Lever Taylor, Billie; Kandiah, Abiramy; Johnson, Sonia; Howard, Louise M.; Morant, Nicola
Abstract: Background: Specialist community perinatal mental health teams support women diagnosed with moderate to severe psychiatric difficulties in pregnancy or postnatally. These teams are being expanded across the UK, and there is considerable international interest in this model of care. However, not all women access these teams, and many are instead supported by community mental health services that do not specialise in the perinatal period. Aims: To explore perinatal women's experiences of specialist perinatal versus generic non-perinatal community mental health support. Methods: Semi-structured interviews were conducted with 36 women diagnosed with perinatal mental health difficulties who were supported in the community either by a specialist perinatal or general non-perinatal mental health service. Data were analysed thematically. Results: Women felt that specialist perinatal and non-perinatal services alike were under-resourced and somewhat too narrow in their remit, but reported positive experiences across both settings. They particularly valued the specialist expertise offered by perinatal teams, but also valued greater continuity of care over a longer period, which some non-perinatal teams provided. Conclusions: The findings suggest that women who experience perinatal mental health difficulties value specialist perinatal expertise, but that general, non-perinatal teams may also have advantages for some. Further research into optimal care arrangements is merited.